2016
DOI: 10.1155/2016/6198278
|View full text |Cite
|
Sign up to set email alerts
|

Pervasive Investigations of Critical Speed over Weight and Deflection Factors of Shaft Assembly in CNC Ball Screw System

Abstract: The demand for higher productivity requires machine tools to work on the adequate critical speed to have faster and more accurate ball screw system. Ball screw affects severely over the higher rotation speed of the shaft in computer numeric control (CNC) machining centers. This paper deals with an approach to calculate the initial critical speed of the shaft. Critical speed requires significant attention due to its major use in the manufacturing sectors. The impacts of weight on the critical speed of shaft ass… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
5
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
5
1

Relationship

4
2

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 23 publications
(28 reference statements)
1
5
0
Order By: Relevance
“…In the proposed model investigations, it has been observed that rated torque value remains inversely proportional to the lead values. This shows a consistent agreement with the results reported in [18, 28, 29]. Lin and Wu [18] highlighted an approach to utilise modelling for the control error in the CNC machining systems.…”
Section: Analytical Results and Validationsupporting
confidence: 89%
See 1 more Smart Citation
“…In the proposed model investigations, it has been observed that rated torque value remains inversely proportional to the lead values. This shows a consistent agreement with the results reported in [18, 28, 29]. Lin and Wu [18] highlighted an approach to utilise modelling for the control error in the CNC machining systems.…”
Section: Analytical Results and Validationsupporting
confidence: 89%
“…Lin and Wu [18] highlighted an approach to utilise modelling for the control error in the CNC machining systems. This work has been extended towards rigorous assessment of [28, 29] along with static and rated toque for CNC marching centre.…”
Section: Analytical Results and Validationmentioning
confidence: 99%
“…Verma and Belokar (2016) reported CNC machining center evaluation over performance parameters. Verma and Belokar (2016) extended by finding the accuracy the deployed model incorporating overall CNC machining center evaluation. Overall, all the graphs reflect linear progressive behaviors and show a strong relationship among pre-loading factor of ball screw and accuracy of feed drive system in CNC machining centers.…”
Section: Detailed Setup and Analytical Results Validationmentioning
confidence: 99%
“…Next, thermal shift of main spindle in XZ (horizontal), YZ (vertical) and axial plane has been analyzed. Next, proposed work investigated that among the three planes, thermal shift remains maximum in axial direction on the consistent patterns of references [9][10]. In the future, focus of work remains on analysis of spindle from different facets i.e.…”
Section: Discussionmentioning
confidence: 99%